Septocolurnellar suture in closed rhinoplasty - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2007)
Several surgeons advise a variety of tip sutures and describe their own techniques in open approach. Septocolumellar suture is one of them and can be described as a loop suture between the medial crura and caudal septum. Although some of the articles mention that it can be applied in closed rhinoplasty, there is no description of the technical details. This paper presents indications, technical steps, and advantages of the septocolumellar suture in closed rhinoplasty. After completing the classic sequence of the endonasal extramucous technique, the medial crural cartilages are dissected from the overlying skin at the midcolumellar level, keeping the distal fibrous attachments between the anterior columellar skin and these cartilages intact. A 510 or 4/0 Prolene (Ethicon Ltd, UK) with a round needle is passed, penetrating both the medial crura and then the caudal septum. Depending on the penetration level of this suture, the tip projection can be increased or decreased, the tip can be rotated, and columellar show can be corrected. This suture also makes the medial crura of the alar cartilages and septum rigidly fixed together, thus providing stability. Depending on the experience gained in 433 primary and 62 secondary rhinoplasty cases since 2000, it can be claimed that this technique, presenting an alternative to the open approach in many cases and expanding the borders of closed approach, allows one to manipulate the tip and columella easily with closed rhinoplasty and provides a significant decrease in the suboptimal results and number of complications.
Keywords: closed rhinoplasty; tip; columella; suture; NASAL TIP; SECONDARY RHINOPLASTY; PART II; 3-STITCH